Measuring Indonesia’s Energy Security Level in the Context of Biodiesel Agroindustry - Firdaus, Alfa; Machfud, Machfud; Suryani, Ani; Achsani, Noer Azam (International Journal of Energy Economics and Policy, 2019)
The development of biodiesel agroindustry in Indonesia is part of the Government’s efforts to achieve national energy security. This study tries to form relevant dimensions and indicators of energy security, which can be used in the context of biodiesel agroindustry. It identified 4 dimensions and 12 indicators of energy security in the context of biodiesel agroindustry, which consisted of availability as measured by energy supply per capita, reserve to consumption ratio and energy diversity; accessibility as measured by feedstock absorption, consumption to production ratio and energy elasticity; affordability as measured by pricing, price volatility and cost of subsidy; efficiency and sustainability as measured by land utilization, CO2 emissions reduction and energy intensity. Based on the energy security index, it is known that the level of national energy security in the context of biodiesel agroindustry over the past 4 years has experienced an increasing trend. Keywords: energy security, agroindustry, biodiesel JEL Classifications: Q41, Q42, Q43 DOI: https://doi.org/10.32479/ijeep.8255